Physical Review A: Atomic, molecular and optical physics. Volume 83, Issue 1, January 2011 - American Physical Society (2011)
Physical Review A provides a dependable resource of worldwide developments in the rapidly evolving area of atomic, molecular and optical physics and related fundamental concepts. The journal contains articles on quantum mechanics including quantum information theory, atomic and molecular structure and dynamics, collisions and interactions (including interactions with surfaces and solids), clusters (including fullerenes), atomic and molecular processes in external fields, matter waves (including Bose-Einstein condensation) and quantum optics. New sections on quantum communication, computation, cryptography and matter waves are growing rapidly.